Biblical text and exegetical culture: collected essays - Fishbane, Michael A. (Forschungen zum Alten Testament, 2022)
Cover -- Title -- Table of Contents -- Abbreviations -- Introduction -- Biblical Israel -- 1. Composition and Structure in the Jacob Cycle (Genesis 25:19-35:22): Formations of Epic Narrative -- 2. Historical Narrative and Narrative Poetics in 1 Samuel 3: Composition and Creativity -- 3. Prophetic Loneliness and Anguish in Jeremiah 20:7-12 : Suffering and Subjectivity -- 4. Creation, Torah, and Hope: The Theological Construction of Psalm 19 -- 5. Biblical Prophecy as a Religious Phenomenon -- 6. Israel and the "Mothers" -- 7. Varia Deuteronomica -- 8. Biblical Colophons, Textual Criticism, and Legal Analogies -- 9. Accusations of Adultery: A Study of Law and Scribal Practice in Numbers 5:11-31 -- 10. Census and Intercession in a Priestly Text (Exodus 30:11-16) and in its Midrashic Transformation -- 11. Form and Reformulation of the Biblical Priestly Blessing (Numbers 6:23-27) -- 12. Inner-Biblical Exegesis: Types and Strategies of Interpretation in Ancient Israel -- 13. Revelation and Tradition: Aspects of Inner-Biblical Exegesis -- 14. Hermeneutical and Spiritual Transformations of "Torah"-Instruction in Biblical and Rabbinic Tradition -- 15. Law to Canon : Some "Ideal-Typical" Stages of Development -- Transition -- 16. The Qumran Pesher and Traits of Ancient Hermeneutics -- 17. Use, Authority, and Interpretation of Mikra at Qumran -- 18. The Well of Living Water: A Biblical Motif and its Ancient Transformations -- 19. Through a Looking Glass: Reflections on Ezekiel 43:3, Numbers 12:8, and 1 Corinthians 13:8 -- 20. From Scribalism to Rabbinism: Perspectives on the Emergence of Classical Judaism -- Ancient Judaism -- 21. Midrash and the Meaning of Scripture -- 22. Exegetical Theology and Divine Suffering in Jewish Thought -- 23. Five Stages of Jewish Myth and Mythmaking.